2014
DOI: 10.1080/00032719.2014.898155
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cigarette Smoke by Headspace Solid Phase Microextraction Gas Chromatography–Mass Spectrometry

Abstract: This paper reports the analysis of the combustion products from moderate and low-tar cigarettes. The compounds were collected by a solvent trap coupled with automatic headspace solid phase micro-extraction and gas chromatography-mass spectrometry (GC-MS). The fiber, solvent system, extraction temperature, and extraction time were investigated by orthogonal experimental design. The optimized conditions included the use of an 85 lm carboxen/polydimethylsiloxane fiber, tert-butyl methyl ether as the solvent, an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Several other GC/MS studies have also revealed that main‐stream cigarette smoke contains more than hundreds of compounds, including phenols, volatile carboxylic acids, long‐chain fatty acids, pyridines, hydroxycarboxylic acid and benzoic acids . Several studies have also detected pentadecanoic acid and phytol as constituents in collected cigarette smoke . The collected material consisted of a brown deposit that may include some tar and cigarette ash as well .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Several other GC/MS studies have also revealed that main‐stream cigarette smoke contains more than hundreds of compounds, including phenols, volatile carboxylic acids, long‐chain fatty acids, pyridines, hydroxycarboxylic acid and benzoic acids . Several studies have also detected pentadecanoic acid and phytol as constituents in collected cigarette smoke . The collected material consisted of a brown deposit that may include some tar and cigarette ash as well .…”
Section: Resultsmentioning
confidence: 98%
“…[54][55][56] Several studies have also detected pentadecanoic acid and phytol as constituents in collected cigarette smoke. [57,58] The collected material consisted of a brown deposit that may include some tar and cigarette ash as well. [59] It is important to note that in our simple collection method, the cigarette smoke was captured on a filter cartridge that may not trap all of the particulate or the more volatile compounds.…”
Section: Resultsmentioning
confidence: 99%